Lista preliminar de coleópteros acuáticos del estado de Morelos, México - Arce-Pérez, Roberto (Instituto de Ecología, A.C., 1995)
Literature on the aquatic Coleoptera of the State of Morelos, México, is reviewed and argumentedby new information. The 54 genera and 1 10 species now known are listed; they represen 45 % and 18.86 % respectively of the totals now knows for México. A diagram shows how the families of aquatic Coleóptera of the State of Morelos aré distributed in relation to the Mexican Transitional Zone, and North And South America.